Effects of COVID-19 Outbreak to the Sales of Traditional Businesses at Novaliches Quezon City S.Y 2021-2022: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to Donthu and Gustaffson (2020), Numerous tourism and hospitality markets no longer exist. Just one family member was allowed to leave the house to prevent the virus, known as "COVID-19," from spreading. The Philippines' entire street became a ghost town where no one could escape. Therefore, sales of Traditional Businesses are greatly affected. The Descriptive Qualitative Design is used and suitable in this study. This study aims to determine the effects of the COVID-19 outbreak on Traditional Businesses in Novaliches, Quezon City. The instruments used in this study are survey questionnaires to gather data and get information from a set of individuals. The researchers used purposive sampling, in which Business owners are selected based on the purpose of the study. The results reveal that most business owners and sellers are 18-23. It also shows that the outbreak hurts traditional businesses. Moreover, they experience various issues regarding their marketing strategy, pricing, and quality. Therefore, researchers give recommendations to solve and improve their sales. In the light of findings and results, researchers recommend to business owners, future business owners, students, community, and future researchers to be prepared, study more about effects, specifically the sales, and develop strategies to survive problems in uncertain situations.
Keywords: COVID 19; Outbreak; Owners; Sellers; Sales; Strategy; Traditional Businesses; Quality